(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Aging is a complex biological process characterized by progressive structural and functional alterations in organs of the immune system. The spleen, as a major peripheral lymphoid organ, plays a key role in immunological surveillance, antigen presentation, lymphocyte proliferation, and hematopoietic regulation. Age-related involution of splenic lymphoid tissue is associated with decreased immune responsiveness and remodeling of stromal and vascular components; however, detailed morphometric characterization of these changes remains insufficiently described in experimental models.